2015
DOI: 10.15835/nsb.7.1.9478
|View full text |Cite
|
Sign up to set email alerts
|

MtDNA Barcode Identification of Finfish Larvae from Vellar Estuary, Tamilnadu, India

Abstract: Planktonic larvae were captured in the shallow Vellar estuary, Tamilnadu, India, during January to June 2013 using zooplankton net. Larvae were identified to the species level by comparison with Genbank data base using MtDNA sequence data. Further analysis showed that there is no sequence variation within-species, whereas between-species variation was more than 25%, supporting the suitability for species identification. The highest genetic distance was observed between A. nigropunctatus and M. cephalus (0.434)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…High resolution of the partial sequences of the COI gene on separating among morphotypes could be due to that this gene has a high mutation rate, which leads to high phylogenetic resolution. A similar result was also reported from various animals such as on Calanoid Arthropod (Hebert et al, 2003b, Australian fishes (Ward et al, 2005;Pegg et al, 2006); Indian fish (Thirumaraiselvi et al, 2015) and grouper species (Nuryanto and Pramono, 2015). The success of our study on larval identification directly provides information on fish species that utilize Segara Anakan as nursery and spawning ground which was formerly not available in that area.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…High resolution of the partial sequences of the COI gene on separating among morphotypes could be due to that this gene has a high mutation rate, which leads to high phylogenetic resolution. A similar result was also reported from various animals such as on Calanoid Arthropod (Hebert et al, 2003b, Australian fishes (Ward et al, 2005;Pegg et al, 2006); Indian fish (Thirumaraiselvi et al, 2015) and grouper species (Nuryanto and Pramono, 2015). The success of our study on larval identification directly provides information on fish species that utilize Segara Anakan as nursery and spawning ground which was formerly not available in that area.…”
Section: Resultssupporting
confidence: 84%
“…Moreover, Nuryanto et al (2007) reported that variable genetic divergence values were observed among giant clams, with range values from 5 % up to 19%. Thirumaraiselvi et al (2015) reported that genetic divergence of more than 25% was observed among fish larvae from Vellar Estuary, India. opportunity to the researchers by approving the funding for this study.…”
Section: Resultsmentioning
confidence: 99%
“…Longer DNA lengths will provide more efficient identification labels [13]. Researchers have demonstrated that genetic barcoding has been beneficial in population genetic studies on invertebrates [18] [19] [20] and vertebrates [21] [22], such as fish [23] [24] [25]. Barcoding has the ability to detect both interspecies and intraspecies variation [26], [27] whether genetic samples are obtained from larval, juvenile or adult life stages [26] [28] Open Journal of Genetics [29].…”
mentioning
confidence: 99%
“…Previous nationalised efforts to barcoding the marine diversity (Lakra et al, 2010;Bineesh et al, 2014;Bamaniya et al, 2015) along with localised efforts to barcode the diversity of Vellar estuary (Khan et al, 2010(Khan et al, , 2011PrasannaKumar et al, 2012;Thirumaraiselvi et al, 2015;Rajthilak et al, 2015;Rahman et al, 2013Rahman et al, , 2019Hemalatha et al, 2016;Sahu et al, 2016;Palanisamy et al, 2020;Manikantan et al, 2020;Thangaraj et al, 2020;Narra et al, 2020) resulted in strengthening the reference library which insured that no ambiguous sequences were present in this study (as all sequences were identified to species level). Identification success was likely due to the use of previously generated references sequences from Indian waters from morphologically verified species and published through reference databases (such as GenBank and BOLD).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to capture potential genetic variation, including undocumented cryptic diversity, it is important to sequence an adequate number of individuals from across a species range (Weigt et al 2012b). We have made considerable efforts in the past decade as part of the Indian Census of Marine Life (ICoML) to recover barcodes in reasonable numbers of marine phyla including fin & shell fishes, invertebrates (Khan et al, 2010(Khan et al, , 2011PrasannaKumar et al, 2012;Thirumaraiselvi et al, 2015;Rajthilak et al, 2015;Rahman et al, 2013Rahman et al, , 2019Hemalatha et al, 2016;Palanisamy et al, 2020;Manikantan et al, 2020;Thangaraj et al, 2020) and plants (Sahu et al, 2016;Narra et al, 2020) occurring in and around the Vellar estuary. Hence we predict a high rate of success in identification of dietary items of A. maculatus occurring in this environment.…”
Section: Introductionmentioning
confidence: 99%